DESAIN DAN SIMULASI GENERATOR LISTRIK TENAGA MANUSIA UNTUK PENGISIAN DAYA TELEPON GENGGAM DENGAN METODE GENERATOR MOTOR LINEAR - Andreas Luis; Daniel Wolo; Richardo Barry Astro (Jurnal Fisika : Fisika Sains dan Aplikasinya, 2022)
Research has been carried out on the design and simulation of human power plants to charge mobile phones. The generator is designed as a linear generator motor due to ergonomic considerations. A case study was conducted on a charging 2000mAh battery. The results showed that at a voltage of 5 Volts, a current of 4 Ampere with 1 hour of use was able to charge 20% of the 2000 mAh battery. While at a voltage of 4 Volts and a strong current of 3 Ampere, the electric current is used to charge the 2000 mAh battery by 15% battery power.